Examining the Judicial Independence and Separation from Executive in Arunachal Pradesh: A Legal Analysis (International Journal of Food and Nutritional Sciences, 2023)
This paper explores the historical journey of the judicial system in Arunachal Pradesh, India, tracing its origins from ancient times. Initially, various regions in India functioned under monarchical rule, with their unique systems of dispute resolution known as Darbars, primarily guided by the principles of Dharma. With the Mughal invasion, a new judicial system was established across different states. Subsequently, the British introduced the court system as the primary institution for dispute resolution in India. Even during this transitional period, Arunachal Pradesh had its own decentralized judicial administration at the village level, employing diverse methods such as the Chicken Liver Test, ordeals, oaths using tiger teeth, swords, stones, and more. The arrival of the British gradually impacted the culture and traditions of the region. Eventually, the area was designated as the North-East Frontier Agency (NEFA) for administration purposes. In 1945, the Assam Frontier (Administration of Justice) Act was enacted, outlining the establishment and appointment of Village Authorities responsible for administering justice. This legislation defined the powers, functions, dispute settlement procedures, and provisions for appeals within the village authority framework. In 1987, Arunachal Pradesh was declared a separate state, leading to a gradual separation of the judiciary from the executive and the establishment of courts. Presently, both systems—village councils (known by various names) and the court system—coexist for dispute resolution in Arunachal Pradesh. The region exhibits a need for specific customary laws, and several tribes have published their own Customary Laws that differ from the nationally established legal framework. Notably, the Government of Arunachal Pradesh recently passed the Arunachal Pradesh Civil Code Bill, introducing a novel dimension to the dispute resolution mechanism in the state.